Equienergetic Graphs Using Cartesian Product and Generalized Composition - Ramane, Harishchandra S.; Patil, Daneshwari; Ashoka, K.; Parvathalu, B. (Sarajevo Journal of Mathematics, 2022)
The energy of a graph is the sum of the absolute values of its eigenvalues. Two graphs of same order are said to be equienergetic if they have same energy. Several papers dealing with equienergetic graphs exists in the literature and most of these papers consists of equieneregtic regular graphs. In this paper we give regular as well as non-regular, equieneregtic graphs using the Cartesian product and also by generalized composition through equitable partition.